Daerah Asal dan Arah Migrasi Orang Minangkabau di Provinsi Jambi Berdasarkan Kajian Variasi Dialektal - Nadra, Nadra; Reniwati, Reniwati; Yades, Efri (Makara Human Behavior Studies in Asia, 2008)
This article is aimed to reveal the original homeland of Minangkabau people in Jambi Province and to trace their migration area based on dialectal variation. For that purpose, the research used the method of dialectometry by applying the technique of permutation. Based on this technique, it is found that in Jambi Province, there are many tendencies of the origines and directions of migration. The points of observation in Jambi which show the level of relation in the difference of pronunciation reveal that there are three tendencies of the pattern of the origines and directions of migration. Meanwhile, the points of observation which show the level on relation in the difference of subdialect shows more tendencies. There are seven patterns.